And life will win: Andean myth and Christian faith in Los zorros by José María Arguedas - Del Mastro Puccio, César (2006)
In his last novel, The Fox from Above and the Fox from Below (1969), José María Arguedas integrates elements of mythical-Andean and religious-Christian discourse, in an effort to enunciate modernity from the place of emigrants from the sierra. . These have become the oppressed of the coast by a capitalist system that threatens to uproot them from their values ​​and culture, a fact that also constitutes the promise of a different future for Peru.